Determination of metronidazole in a rat stomach by HPLC for obtaining basic data of the eradication therapy of Helicobacter pylori - Mai Kubodera; Tadakazu Tokumura; Yoshiharu Machida (Elsevier, 2012)
In the eradication therapy of Helicobacter pylori changes of antibiotics as these concentrations or amount in the stomach after oral administration were not clear. A simple and accurate method for determining the concentration of metronidazole (MTZ) in homogenate of rat stomach was developed in order to obtain basic data to design a pharmaceutical preparation having targeting ability to the surface of gastric-mucosa. This method included a deproteinization process by methanol, separation with reversed-phase high-performance liquid chromatography, and detection with an ultraviolet wavelength of 370Â nm. Regression analysis showed that the method was linear over a standard curve range from 5Â Î¼g/mL to 2000Â Î¼g/mL. The inter-day precision and accuracy values between the ranges were 5.0% or better and â7.5 to 5.2%, respectively. The newly developed method was applied to an analysis of gastric samples after oral administration of MTZ at a dose of 5Â mg/kg. It was found that the residual MTZ in the stomach was determined within 5Â h after dosing. This method is useful for monitoring MTZ in stomach after its oral administration to rats. Keywords: Metronidazole, HPLC, Homogenate, Stomach, Rat